PERANCANGAN SISTEM INFORMASI PEMESANAN TIKET TRAVEL BERBASIS WEB DI PT YOSSY MANDIRI - Mulyana, Wide; Izaky Arif Rahman; Meli Aulia; Muhammad Fadly; Nabil Andra Putra; Sintia Hadisty (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2025)
This research aims to design a web-based ticket booking information system that can enhance the efficiency and quality of services at PT. Yossy Mandiri. This system is designed to facilitate customers in making ticket reservations online and assist the admin in managing booking data, departure schedules, and customer information. The system development method used is the waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance. The result of this research is a web-based travel ticket booking information system that can improve efficiency and service quality at PT. Yossy Mandiri. This system is expected to be a solution for the company in enhancing customer service and optimizing internal business processes.